On-line adaptive algorithm with glucose prediction capacity for subcutaneous closed loop control of glucose: evaluation under fasting conditions in patients with Type 1 diabetes - Schaller, H. C.; Schaupp, L.; Bodenlenz, M.; Wilinska, M. E.; Chassin, L. J.; Wach, P.; Vering, T.; Hovorka, R.; Pieber, T. R. (Diabetic medicine, 2006)
Aims  To evaluate an algorithm with glucose prediction capacity and continuous adaptation of patient parameters—a model predictive control (MPC) algorithm—to control blood glucose concentration during fasting conditions in patients with Type 1 diabetes. In the subcutaneous (sc) route within a closed loop system. Methods  Paired experiments were performed in six patients. Over 8 h the MPC algorithm was used to control glucose with s.c. insulin administration and two different glucose monitoring protocols: first, the algorithm was provided with intravenous (i.v.) glucose values for insulin dosage calculation directly (i.v.–s.c. route). Then, in the second experiment, i.v. glucose values were fed to the MPC with a delay of 30 min to simulate s.c. glucose measurements (‘s.c.’–s.c. route). In both experiments plasma glucose, insulin dosage, and serum insulin levels were analysed. Results  Glucose concentration was brought from hyper‐ to normoglycaemia and kept in the physiological range (6–7 mmol/l) with both routes in all subjects. Mean glucose concentration reached the threshold of 7 mmol/l approximately 2 (i.v.–s.c. route) and 3 (‘s.c.’–s.c. route) hours after the start of glucose control with the MPC. During the last 2 h of automated glucose control, mean glucose concentration was 6.3 ± 0.2 mmol/l and 6.6 ± 0.3 mmol/l for i.v.–s.c. and ‘s.c.’–s.c. route, respectively. Glucose concentration, insulin doses, and serum insulin levels did not differ significantly between routes (P > 0.05). Conclusions  The MPC algorithm is suitable for glucose control during fasting within an extracorporeal artificial β‐cell in the subcutaneous route Type 1 diabetic patients.